2019
DOI: 10.1093/ofid/ofz136
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of T2Candida Among ICU Patients With Risk Factors for Invasive Candidiasis

Abstract: Background Invasive candidiasis (IC) comprises candidemia and deep-seated candidiasis. Blood culture (BC) is the gold standard test, but sensitivity is low. T2Candida is a new diagnostic test. We investigated the performance of T2Candida, BC, and Candida mannan antigen (MAg) for detection of IC in a high-risk intensive care unit (ICU) population. Methods One-hundred twenty-six ICU patients at high risk of IC with sepsis despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 42 publications
4
42
0
1
Order By: Relevance
“…Direct comparison of the diagnostic values with other published methods specific for detection of Candida is complex due to the unique settings of each clinical study. Nevertheless, one recent study assessing the T2Candida approach showed a lower specificity of <60% for high-risk ICU patients compared to data shown here [23]. Another study reported a sensitivity of 43% and a specificity of 94% for the T2 system for a patient cohort receiving empirical antifungal treatment [31].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Direct comparison of the diagnostic values with other published methods specific for detection of Candida is complex due to the unique settings of each clinical study. Nevertheless, one recent study assessing the T2Candida approach showed a lower specificity of <60% for high-risk ICU patients compared to data shown here [23]. Another study reported a sensitivity of 43% and a specificity of 94% for the T2 system for a patient cohort receiving empirical antifungal treatment [31].…”
Section: Discussionmentioning
confidence: 52%
“…This test is based on amplification, hybridization, and detection of pathogen nucleic acids [22]. The T2-System (T2 Biosystems, Lexington, Massachusetts, United States) uses magnetic resonance analysis to confirm candidemia [23]. The advantages of such molecular approaches are the superior sensitivity and the speed compared to culture-based testing [15].…”
Section: Introductionmentioning
confidence: 99%
“…151 In a study conducted in 126 ICU patients at high risk of IC and with sepsis despite 3 days of broad-spectrum antibiotics, the sensitivity and specificity of the T2Candida panel for proven IC were 55 and 93%, respectively, with 50% PPV and 93% NPV. 152 In another study conducted among 46 patients with severe sepsis or septic shock and multiple risk factors for candidemia, the T2Candida panel showed 100% sensitivity (95% CI: 2.5-100), 92% specificity (95% CI: 78-98), 25% PPV (95% 1-81), and 100% NPV (95% CI: 90-100). 153 Of note, some authors have also suggested that a positive T2Candida test could be a potential marker of poor outcome in patients receiving empirical antifungal therapy for suspected IC.…”
Section: Rapid Tests Based On Polymerase Chain Reactionmentioning
confidence: 98%
“…Arendrup et al recently conducted another prospective study with 126 ICU patients which were classified into groups of proven, likely, possible, or unlikely IC based on the results of BC, culture from sterile sites, colonization, a Candida antigen assay, and clinical findings. Compared with BC and the antigen test, the T2Candida Panel had the highest sensitivity for the detection of IC [ 62 ], even though the sensitivity was lower than observed in the 2015 Mylonakis et al study [ 61 ]. The best sensitivity was achieved by a combination of BC and the T2Candida Panel [ 62 ].…”
Section: Blood Culture Independent Molecular Diagnosticsmentioning
confidence: 99%
“…Compared with BC and the antigen test, the T2Candida Panel had the highest sensitivity for the detection of IC [ 62 ], even though the sensitivity was lower than observed in the 2015 Mylonakis et al study [ 61 ]. The best sensitivity was achieved by a combination of BC and the T2Candida Panel [ 62 ]. As the test also detects non-viable cells, T2MR might be a useful tool for the monitoring of candidemia upon initiation of antifungal therapy.…”
Section: Blood Culture Independent Molecular Diagnosticsmentioning
confidence: 99%